Extracellular matrix glycation epigenetically regulates brain aging and neurodegeneration in the in vitro aged neurovascular model - Jang, Minjeong; Lee, Hae-June; Seo, Eun U.; Kim, Hong Nam (Elsevier Science Inc., 2026)
As life expectancy continues to rise, addressing aging and age-related diseases becomes crucial for maintaining a healthy lifestyle. Advanced glycation end-products (AGEs) accumulate in brain tissue as we age, co-localizing with amyloid (3 and tau in the brains of elderly and Alzheimer's disease patients. However, the link between increased AGE levels, aging, and neurodegeneration remains unclear. To explore the effect and mechanism of AGEs on the brain, we developed a neurovascular (NV) model that reflects features of an aged brain by integrating an AGE-anchored matrix. Under AGE-incorporated conditions, we observed brain endothelial dysfunction and microglial activation, leading to increased neuroinflammation and neurodegeneration. Notably, we discovered that targeting AGE and its receptor could attenuate AGE-mediated neurodysfunction through the histone-modifying enzyme, KMT2A, in neurons within an aged NV model. Our findings in the NV model align with those observed in aged and Alzheimer's disease mouse models. This aged brain model offers a valuable platform for elucidating the epigenetic mechanisms of brain aging and provides insights into novel anti-aging strategies for age-associated brain disorders.